2013
DOI: 10.1165/rcmb.2012-0462oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Antifibrotic Mechanisms Aspirin-Triggered Lipoxin A4 Synthetic Analog

Abstract: No successful therapies are available for pulmonary fibrosis, indicating the need for new treatments. Lipoxins and their 15-epimers, aspirin-triggered lipoxins (ATL), present potent antiinflammatory and proresolution effects (Martins et al., J Immunol 2009;182:5374-5381). We show that ATLa, an ATL synthetic analog, therapeutically reversed a well-established pulmonary fibrotic process induced by bleomycin (BLM) in mice. We investigated the mechanisms involved in its effect and found that systemic treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…This is supported by a study showing the role of lipoxins in cell therapy‐mediated lung repair, where human bone‐marrow‐derived MSCs induced production of LXA4 by alveolar epithelial cells in a mouse model of LPS‐induced acute lung injury []. Guilherme and colleagues showed that LXA4 analogs were potent anti‐inflammatory and antifibrotic compounds in a bleomycin‐induced model of lung injury []. We thus focused our attention on lipoxin A 4 a key regulator of macrophage infiltration and function in hAEC‐mediated repair of lung fibrosis.…”
Section: Discussionmentioning
confidence: 86%
“…This is supported by a study showing the role of lipoxins in cell therapy‐mediated lung repair, where human bone‐marrow‐derived MSCs induced production of LXA4 by alveolar epithelial cells in a mouse model of LPS‐induced acute lung injury []. Guilherme and colleagues showed that LXA4 analogs were potent anti‐inflammatory and antifibrotic compounds in a bleomycin‐induced model of lung injury []. We thus focused our attention on lipoxin A 4 a key regulator of macrophage infiltration and function in hAEC‐mediated repair of lung fibrosis.…”
Section: Discussionmentioning
confidence: 86%
“…Bleomycin is an important chemotherapeutic agent but carries a known risk of pulmonary fibrosis. Treatment with LXA 4 or 15-epi-LXA 4 results in an attenuation of pulmonary fibrosis in animals exposed to bleomycin through reduction of the pro-fibrotic cytokine TGFβ 132 , as well as an increase in the prevalence of M2 macrophages 133 , both resulting in decrease fibrotic matrix and improved pulmonary function. In humans, scleroderma lung disease is characterized by idiopathic progressive lung inflammation and fibrosis and, of interest, patients with scleroderma lung disease underproduce pro-resolving mediators, in comparison to their pro-inflammatory counterparts 134 .…”
Section: Spms In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…15,16 Furthermore, there are publications showing strong beneficial effects of lipoxin A4 or its more stable analogs in preventing myofibroblast formation 17 and bleomycin-induced fibrosis 18 and in improving lung function of bleomycin-treated mice. 19 Interestingly, CD45 1 fibrocytes, which show mesenchymal properties such as collagen type 1 or fibroblast specific protein 1 (FSP) expression, 20 have been suggested to express E-type prostanoid 2 (EP2), EP4, and I-type prostanoid receptors. 21 Abbreviations It has been demonstrated that patients with IPF show significantly lower levels of PGs, particularly PGE 2 , in the bronchoalveolar lavage (BAL).…”
mentioning
confidence: 99%